Studi Numerik dan Eksperimental Aliran 3-D pada Kombinasi Airfoil Pelat Datar dengan Variasi Permukaan Bawah dan Pengaruh Celah - Gunawan Nugroho; Herman Sasongko (Institute of Research and Community Outreach, Petra Christian University, 2005)
Recently, the complexity of 3-D flow around airfoil/flat plate junction at endwall region has attracted many researchers of Aerodynamics. The majority of its experimental and numerical observations are conducted to compressor cascade. Because of that importance, stronger conceptual basis of 3-D flow is required, so the present study has stressed on single body airfoil/flat plate which clearance effect is exist. Variation of angle of attack and geometry on lower surface in this research have been carried out numerically and experimentally. Numerical study has been implemented by putting inlet velocity 25 m/s as initial condition while air density and viscosity are assumed constants. Trends of coefficient of pressure and velocity vector are studied accurately. Experimental study was conducted in wind tunnel with inlet velocity 25 m/s by means of measurement of static pressure on wall and airfoil which endwall and midspan are included. Two previous methods were supported by flow visualisation in the manner of examining the details of skin friction line. It was evidenced that 2-D history flow was strongly influenced 3-D flow characteristics. It was clarified by lower surface variation and by usage of wider blade thickness model, that was when incoming flow attached to leading edge would experience stronger adverse pressure gradient with the result that separated earlier and so was when it pass more curved surface, stronger adverse pressure gradient is responsible for generating greater pressure difference between upper and lower surface and finally, tip clearance flow is induced more intensivelly. Those effects are amplified when angle of attack is applied. Saddle point is formed further away in front of leading edge and tend to move on pressure side below, Wider branch separation line is detected and jet flow is amplified. Abstract in Bahasa Indonesia : Kompleksnya aliran 3-D pada daerah endwall dan ujung dari kombinasi airfoil/plat datar telah menarik perhatian para peneliti di bidang Aerodinamika pada tahun-tahun belakangan ini. Penelitian aliran 3-D dilakukan terutama pada kompresor kaskade baik secara eksperimental maupun numerik. Oleh karena itu, untuk memberikan dasar yang lebih kokoh, penelitian ini menitikberatkan pada kombinasi airfoil tunggal/plat datar dengan memberikan pengaruh celah. Penelitian ini dilakukan secara numerik dan eksperimental dengan melakukan variasi geometri pada permukaaan bawah dan sudut serang 00. Dalam studi numerik, kerapatan dan viskositas udara dianggap konstan serta aliran masukan sebesar 25 m/s. Parameter- parameter yang diperhatikan dalam analisa adalah tekanan statik, tekanan dinamik, kecepatan, dan tegangan geser. Studi eksperimental dilakukan pada wind tunnel dengan kecepatan aliran masukan 25 m/s dengan daerah pengukuran tekanan statik pada dinding dan badan airfoil yang meliputi ujung dinding, ujung celah dan tengah badan airfoil. Visualisasi aliran dilakukan untuk mendukung studi numerik dan pengukuran tekanan statis dengan melihat detil konfigurasi garis gesekan kulit. Dari penelitian didapatkan bahwa formalisme 2 D flow terbukti sangat mempengaruhi karakteristik aliran 3 dimensi. Variasi permukaaan bawah dan penggunaan model dengan ketebalan bilah yang besar menegaskannya, yaitu aliran yang menuju ujung depan akan mengalami gradien tekanan balik yang lebih besar sehingga aliran akan lebih cepat terpisahkan dan begitu juga jika aliran melewati kontur lebih lengkung, gradien tekanan balik yang lebih besar menginduksikan ujung celah flow yang lebih kuat Kata kunci: Titik sadel, ujung-celah, aliran jet, gradien tekanan balik dan vortex ujung celah.